Qualidade de sementes de soja e incidência de Sclerotinia sclerotiorum (lib) de Bary em função do beneficiamento e armazenamento - Teles, Héria de Freitas (2012)
Soybean (Glycine max L. Merrill) is considered the worldwide leader in oilseed production and consumption, and currently the main source of vegetable protein available. In the field, the crop is infected by a large number of diseases. Among the fungal diseases, the white mold, caused by Sclerotinia sclerotiorum (Lib) de Bary, has emerged as one of the most serious, affecting the quality of seed, which can also be influenced by processing and storage. The pathogen survives in soil through resistance structures (sclerotia) and can attack more than 400 host species. The objective of this study was to evaluate the physical and physiological quality and S. sclerotiorum incidence of soybean seeds during processing and six months after in cold and dry storage and environment conditions. Seeds from eight cultivars, coming from production fields, naturally infested with S. sclerotiorum, located in Vianópolis, Silvânia, Luziânia and Orizona in the State of Goiás, in the seasons 2009/2010 and 2010/2011 were studied. Samples were collected at each stage of processing: in the hopper (reception), after pre-cleaning, discard one (precleaning), after cleaning, after the sieve classifiers (three sieve sizes), after the spiral (three sieve sizes), after gravity table (three sizes of sieve) and final disposal, totalizing 14 samples. The following analysis were done: moisture content, physical purity, germination and tetrazolium test, and tests for S. sclerotiorum detection in rolled paper and Neon method. PCA analysis was performed and Pearson correlations study between the averages of the variables in processing stages for each cultivar. Processing improves physical and physiological quality of soybean seeds, which is efficient for S. sclerotiorum control, eliminating the sclerotia associated to the seeds and reducing the amount of inoculum that could return to the planting area. Physical purity, germination, viability and vigor are positively correlated together and negatively with the mass of sclerotia. Processing also reduces significantly the inoculum potential in the mycelial form of S. sclerotiorum in the seeds. Storage does not influence the incidence of S. sclerotiorum in mycelial form in seeds, which can increase or not during this period, regardless the storage conditions, in a cold and dry storage or in environment condition.